2012
DOI: 10.1097/brs.0b013e318257f12a
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cage Retropulsion After Posterior Lumbar Interbody Fusion

Abstract: These results indicate that PLIF at L5/S, a wide disc space with instability, multilevel fusion surgery, and a pear-shaped disc space on lateral radiographs are risk factors for cage retropulsion. The identification of these risk factors should allow us to avoid this complication, and the use of expandable cages is an effective option for such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
97
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 21 publications
9
97
0
4
Order By: Relevance
“…Moreover, Kimura et al reported that a PLIF at the level L5/S1, a wide disc space with instability, multilevel fusion surgery, and a pear-shaped disc space on lateral radiographs are risk factors for a cage retropulsion (Table 1) [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Kimura et al reported that a PLIF at the level L5/S1, a wide disc space with instability, multilevel fusion surgery, and a pear-shaped disc space on lateral radiographs are risk factors for a cage retropulsion (Table 1) [3].…”
Section: Discussionmentioning
confidence: 99%
“…Less frequently, cage migration and/or cage subsidence may occur months to years after lumbar interbody fusion procedures. Besides a putative development of a segmental kyphosis and a disposition to pseudoarthrosis, these complications can lead to progressive compression of nervous structures, resulting in disabling recurrent pain and/or significant sensori motor sequelae, necessitating revision surgery [3].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is associated with higher risks of cerebrospinal fluid leakage, dysesthetic nerve pain syndrome, nerve root injury, epidural fibrosis, as well as cage migration [9][10][11].In our study, multivariate analysis was used to account for potential covariates and identify factors associated with an increased complication risk -the only peri-operative complications occurred in the PLIF group, with 2 cases of dural tears, 2 cases of epidural hematomas, and 2 cases of dysesthetic nerve pain syndrome secondary to genitofemoral nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…The authors believe that this is due to the angle of L-5 with respect to S-1-which is generally higher than any other lumbar segment. 1,19,28,36 To achieve this angle, the anatomy is such that the posterior edge of the annulus is shorter in height than the anterior. 39 The authors believe that this shorter annulus could affect the intact rigidness by resisting compressive loads, which would cause higher stiffness.…”
Section: Discussionmentioning
confidence: 99%